Enhancing Vocational High School Students' Oral Communication Skills through Project-Based Learning: A Case Study - Asep Samsudin; Rindya Santi Utami (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
In today’s communication-driven workforce, vocational students must possess strong oral communication skills alongside technical expertise. This study investigates English teachers' perceptions of Project-Based Learning (PBL) as a pedagogical approach to enhance speaking skills in vocational high schools. Grounded in constructivist theory of PBL model, the research employed a descriptive qualitative method through semi-structured interviews with four English teachers in Jember. The findings reveal that teachers generally perceive PBL as effective in fostering oral communication due to its emphasis on real-world application, collaboration, and student autonomy. However, significant challenges were identified, including limited teacher experience with PBL, student reluctance to speak, and a need for structured reflection strategies. Teachers proposed adaptive strategies to support engagement and reflection, showing a willingness to integrate PBL more fully with appropriate support. The study underscores the importance of professional development, curriculum flexibility, and institutional support to optimize PBL implementation, affirming its significant role in equipping vocational students with essential communication skills for their future careers.